Investigating Students’ Language Learning Strategies During Online Learning: How They Deal with Speaking Ability - Marlin; Andang Saehu; Audi Yundayani (JEELS (Journal of English Education and Linguistics Studies), 2021)
The pandemic situation shifted the learning process from offline to online. It challenges the students in English learning, especially in learning their speaking ability. However, the students manipulated the strategies by utilizing online platforms or mobile phone applications accordingly to their learning experience. This study investigates students' language learning strategies and how the strategy is applied in learning speaking ability. The case study was carried out in a senior high school. The respondents 64 were chosen purposively to be involved in this study. The instruments of data collection were conducted by questionnaire and interview under Strategy Inventory for Language Learning (SILL). The results showed that 63 (95%) of students used metacognitive strategies in the form of centering learning process, arranging, and planning learning strategies. Moreover, 61 or 91% of students applied practicing, receiving, and sending messages of group cognitive strategies to motivate them to practice their speaking ability during online learning. Furthermore, less than 80% applied social, memory, affective, and compensation. It recommended that the teacher be a facilitator by providing a good stimulus for the students to motivate themselves to be self-regulated.